Controllable acidophilic dual-emission fluorescent carbonized polymer dots for selective imaging of bacteria. Issue 19 (3rd May 2019) - Zhao, Xiaohuan; Tang, Qiuling; Zhu, Shoujun; Bu, Wenhuan; Yang, Mingxi; Liu, Xinchan; Meng, Yang; Yu, Weixian; Sun, Hongchen; Yang, Bai
Abstract : Red/blue dual-emission carbonized polymer dots (CPDs) were synthesized. Due to their sensitive acidophilic properties, selective imaging of bacteria was achievable without further modification of CPDs. Abstract : Fluorescent materials can be powerful contrast agents in photoelectric devices and for bioimaging. As emerging fluorescent materials, carbonized polymer dots (CPDs) with high quantum yields (QYs), long-wavelength emission and multiple functions are highly desired. Despite great progress in the synthetic methods and QYs of CPDs, multiple emission of CPDs is challenging. Therefore, we developed CPDs with dual-emission fluorescence in terms of inherent blue and red emission. In addition, CPDs with sole blue emission (B-CPDs) and red emission (R-CPDs) were synthesized, respectively, by regulating the reaction conditions to control the quantitative structure and emission centers. The absolute QY of R-CPDs in water was 24.33%. These three types of CPDs with dual/sole emission could be used in optoelectronic and bioimaging applications. With different CPDs coated on a commercially available gallium nitride light-emitting diode chip as a color-conversion layer, LEDs with blue, yellow, and red emission were achieved. Benefiting from the different emission intensities and emission peaks of R/B-CPDs in different pH conditions, they were used (without further modification) to distinguish between Porphyromonas gingivalis, Streptococcus mutans, Escherichia coli and Staphylococcus aureus in dental plaque biofilms (the first time this has been demonstrated). These findings could enable a new development direction of CPDs based on the design of multi-emission centers.